Thermal degradation in Carrara marbles as the cause of deformation of cladding slabs - A. Spagnoli; M. Migliazza; M. Zucali; A.M. Ferrero (Fracture and Structural Integrity, 2014)
Marble slabs, typically used as façade panels to externally cover buildings, might permanently deform after a certain time of environmental exposure. This phenomenon, called bowing, is generally accompanied by a reduction of strength which increases with increasing degree of bowing. In the present paper, a theoretical model to calculate the progressive bowing of marble slabs submitted to temperature cycles is briefly recalled and applied to a specific Carrara marble sample. The marble is investigated by a microscopic analysis of thin sections cut along three orthogonal directions. The digital photographs are treated by an image analysis code which is capable of extracting grain size and shape distributions. In this way the anisotropic microstructure of the marble is quantified and taken into account in the numerical analyses. The influence of size distribution of grains as well as of their distribution of optic axis orientation on the slab bowing is discussed with the attempt of offering a quantitative tool for a better understanding of in situ bowing measurements.